Effect of the removal of digestive enzymes and different COS-polyphenol conjugates on the quality of Harpiosquillid mantis shrimp stored in iced water - Mallikarjun Chanchi Prashanthkumar; Xinru Fan; Qiancheng Zhao; Jirakrit Saetang; Yadong Zhao; Bin Zhang; Soottawat Benjakul (Food Chemistry: X)
Harpiosquillid mantis shrimp (HMS) undergoes textural softening caused by trypsin in digestive tract within 2–3 days of iced storage. Chitooligosaccharide (COS) and various COS-polyphenol conjugates containing gallic acid (GAL), caffeic acid (CAF), ferulic acid (FER), catechin (CAT) and epigallocatechin gallate (EGCG) were prepared, characterized and examined for inhibition toward purified HMS trypsin. COS-CAT at 2.5 % showed a maximum inhibition (72.90 %) against purified trypsin. Conversely, COS and individual polyphenols inhibited trypsin activity to a low extent. COS-CAT inhibited autolysis of HMS meat mediated by trypsin as witnessed by more retained protein band intensity and lower α-amino acid content. The incision and drainage of digestive fluids from whole HMS before treated with COS-CAT solution retained the major muscle proteins and sensory acceptability until day 5 in iced water. Thus, the removal of digestive fluid prior to COS-CAT treatment could be a potential means to maintain the quality of HMS.